"A refugee is someone who refused to be oppressed": Self-Survival Strategies of Congolese Young People in Uganda. Issue 1 (28th March 2014) - Clark-Kazak, Christina
Drawing on Ruth Lister's conceptual approach to agency, this paper shows how Congolese young people in refugee contexts in Uganda 'get by', 'get (back) at', 'get out', and/or 'get organized'. These purposeful responses to violence and structural constraints contrast with dominant discourses about refugee young people as inherently vulnerable and in need of protection from outside agencies. The article thus concludes with some suggestions of how researchers, policy-makers, and practitioners can better recognize and support young people's own survival strategies in contexts of violence and displacement.